A administração vis-à-vis valores individuais e organizacionais - Royes, Golber Fernandes (1999)
This paper aims at bringing a new prospect to the administrative knowledge, by pointing out the parcial and instrumental nature developed by organizational theories. Aiming at introducing the understanding about values in the scope of administration, one attempts to do that through the individuaIs' perspective, emphasizing their points of view. In this essay, administration is conceived as a non-neuter social science that has reproduced the values of the system in the organizational environment. In so far as theoretical administrative framework was developed, organizational theories were becoming increasingly complex, subjecting individuaIs to productive demands. On that perspective, adminstration was departing as far its main reason of existence, man, as significative issues ofthis millenium ending. Indeed, administration would have became tecnique, conducting its efforts to satisfy organizational needs, considering man a mere productive agent. This study uses the CriticaI Theory, a proposal of comprehension of society, by carring forward its statements to the organizational scenary, to bring home and to show up the values professed by administrative theories and the characterization of man that each one has developed. Carl Gustav Jung's teachings and his definition corcerning personal and colective unconscious are used to explane why administration has not taken into account another values, that not those that has became hegemonic by the system action, in conscious universe. Next, one attended to set and to associate to the ideas beforehand developed concerning values and organizational theories, the uni verse in which the fieldwork was gotten over, the Brazilian Armed Forces. Eventually, the fieldwork served as a reinforcement for the ideas that beforehand were presented: that organizational theories have privileged another values, that not those of individuaIs, that there is another way to understand reality, more substantive and that, although administration had exert, at least on speech, for answaring individual's basic needs, in organizational context, in fact, has not been successful. The new prospect that this paper aims at presenting refers to the understanding that there are another values, that not those that have been privileged by organizations, that must be taken into account by administrative knowledge. One seeks both to alert administrative theoretical body as regards the social rule which commits administration and to suggest that administration departs instrumentality and comes up substantivity, that is a world vision always possible and so many times disregarded by administration and other self-called social sciences.